Dihydromyricetin improves vascular hyporesponsiveness in experimental sepsis via attenuating the over-excited MaxiK and KATP channels. (1st January 2018) - Peng, Jin; Zhang, Jian; Zhang, Li; Tian, Yonggang; Li, Yahong; Qiao, Lujun
Abstract: Context: Dihydromyricetin (DMY) has oxidation resistance, anti-inflammatory and free radical scavenging capabilities. The preventive effects of DMY for vascular hyporeactivity remain unclear. Objective: This study investigates the preventive effects of DMY in vascular hyporeactivity. Materials and methods: The experimental sepsis was induced by transvenous administration of lipopolysaccharide (LPS) to Sprague–Dawley (SD) rats. DMY-treated rats received daily administration of DMY, 5 μg/kg dissolved in DMSO through the tail vein for 7 days. The invasive mean arterial pressure (MAP) of the caudal ventral artery was measured. Dose-response curves for norepinephrine (NE, doses from 10 −9 to 10 −6  M) were obtained in isolated thoracic aorta in a cumulative manner. The function of MaxiK and KATP channels were investigated using whole-cell patch clamp recording. The Elisa was adopted to measure the serum concentration of NO, MDA, 3-NT, IL-1β and TNF-α. Results: The increased MAP in septic rats induced by vasopressor agents was smaller than that in control rats. However, the % of increased MAP induced by vasopressor agents was raised by DMY injection (NE: 20.4 ± 8.495 vs. 15.16 ± 5.195%; AVP: 14.05 ± 2.459 vs. 9.583 ± 2.982%, p  < 0.05). The vascular hyporesponsiveness to NE (10 −6  M) in vitro. was increased by 51% in LPS + DMY group compared with that in LPS + Con group (2.74 ± 0.81 vs. 1.82 ± 0.92 g, p  < 0.05). Charybdotoxin (a potent MaxiK channel blocker) and glibenclamide (a KATP channel blocker) pretreatment, instead of 4-aminopyridine (4-AP) and BaCl2, could diminish the DMY-induced improvement of vasoconstrictor hyporeactivity (ChTX: 73.2 ± 11.8 vs. 71.8 ± 13.5%; Glib: 63.1 ± 12.5 vs. 58.1 ± 13.7%, p  > 0.05). DMY blunted the highly sensitized MaxiK and KATP channels of arterial smooth muscle cells isolated from the thoracic aorta of LPS rats. DMY decreased the serum level of NO, MDA, IL-1β and TNF-α, which had increased in LPS rats. Discussion and conclusions: Our results indicate that DMY administration ameliorated the impaired contractility of the rat aorta in experimental sepsis. Such an effect is mediated by normalization of the over-excited MaxiK and KATP, channels possibly via oxidative stress inhibition.